Responding to COVID-19 vaccine-related safety events: WHO Western Pacific regional experience and lessons learned (Western Pacific Surveillance and Response, 2023)
Problem: Novel vaccines were developed in an unprecedentedly short time in response to the global coronavirus disease (COVID-19) pandemic, which triggered concerns about the safety profiles of the new vaccines. This paper describes the actions and outcomes of three major adverse events of special interest (AESIs) reported in the World Health Organization’s (WHO’s) Western Pacific Region: anaphylaxis, thrombosis with thrombocytopenia syndrome (TTS) and post-vaccination death.Context: During the large-scale introduction of various novel COVID-19 vaccines, robust monitoring of and response to COVID-19 vaccine safety events were critical.Action: We developed and disseminated information sheets about anaphylaxis and TTS; provided tailor-made training for anaphylaxis monitoring and response, webinars about TTS and AESIs, and an algorithm to support decision-making about AESIs following immunization; as well as provided country-specific technical support for causality assessments, including for possible vaccination-related deaths.Outcome: Each major vaccine event and situation of high concern was responded to appropriately and in a timely manner with comprehensive technical support from WHO. Our support activities have not only strengthened countries’ capacities for vaccine safety surveillance and response, but also enabled countries to decrease the negative impact of these events on their immunization programmes and maintain the confidence of health-care professionals and the general population through proactive delivery of risk communications.Discussion: This paper summarizes selected, major AESIs following COVID-19 vaccination and responses made by WHO’s Regional Office for the Western Pacific to support countries. The examples of responses to vaccine safety events during the pandemic and unprecedented mass vaccination campaigns could be useful for countries to adopt, where applicable, to enhance their preparation for activities related to monitoring vaccine safety.